2021
DOI: 10.3389/fmicb.2021.770385
|View full text |Cite
|
Sign up to set email alerts
|

Human and Animal RNA Virus Diversity Detected by Metagenomics in Cameroonian Clams

Abstract: Many recent pandemics have been recognized as zoonotic viral diseases. While their origins remain frequently unknown, environmental contamination may play an important role in emergence. Thus, being able to describe the viral diversity in environmental samples contributes to understand the key issues in zoonotic transmission. This work describes the use of a metagenomic approach to assess the diversity of eukaryotic RNA viruses in river clams and identify sequences from human or potentially zoonotic viruses. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…This technique was found to efficiently obtain complete genomes of different human enteric viruses in sewage samples and related bioaccumulated oysters (Strubbia 2019). Such an approach was also applied to naturally contaminated clams collected in the Sanaga river (Cameroon) and allowed the detection of a large diversity of RNA viruses including human or animal norovirus sequences (Bonny et al 2021). Here, the method was promising on TSS samples but performed less well on naturally contaminated samples from the BLS and OB sets, presumably due to longer storage and loss of NoV genome integrity.…”
Section: Discussionmentioning
confidence: 99%
“…This technique was found to efficiently obtain complete genomes of different human enteric viruses in sewage samples and related bioaccumulated oysters (Strubbia 2019). Such an approach was also applied to naturally contaminated clams collected in the Sanaga river (Cameroon) and allowed the detection of a large diversity of RNA viruses including human or animal norovirus sequences (Bonny et al 2021). Here, the method was promising on TSS samples but performed less well on naturally contaminated samples from the BLS and OB sets, presumably due to longer storage and loss of NoV genome integrity.…”
Section: Discussionmentioning
confidence: 99%
“…A novel bastrovirus called AtBastV/GCCDC11/2022 was found in the gut samples of Asiatic toads, with similar genomic characteristics to those previously described for BastVs. BastVs is a novel group of hepe-astrovirus-like viruses identified in human stools [ 29 ], raw sewage [ 30 ], pigs [ 31 ], bats [ 32 ], rats, as well as in clams [ 33 ] by metagenomics sequencing. The RNA genome of AtBastV/GCCDC11 consists of three ORFs: ORF1, ORF2, and ORF3.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic analysis was performed using a Nextflow pipeline as previously described ( Bonny et al, 2021 ). For the first part of the analysis, reads from each library as well as reads merged from all four libraries per sample were considered (5 analysis for each sample; Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, most of the time only amplicon-based metagenomic approaches have solved the issue of sensitivity to describe the genetic diversity of one virus genus ( Suffredini et al, 2018 ; Fumian et al, 2019 ; Mabasa et al, 2022 ). In previous works, we found that sample pre-treatment and capture-based enrichment during the library preparation stage allowed the recovery of higher numbers of viral reads and thus the identification of longer viral contigs ( Strubbia et al, 2019 ; Bonny et al, 2021 ).…”
Section: Introductionmentioning
confidence: 98%